2011
DOI: 10.1111/j.1365-2141.2011.08669.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cellular and therapeutic effects of obatoclax in rituximab‐sensitive and ‐resistant lymphomas

Abstract: Bcl-2 proteins represent a rheostat that controls cellular viability. Obatoclax, a BH3-mimetic, has been designed to specifically target and counteract anti-apoptotic Bcl-2 proteins. We evaluated the biological effects of obatoclax on the anti-tumour activity of rituximab and chemotherapy agents. Obatoclax induced cell death of rituximab/chemotherapy-sensitive (RSCL), -resistant cell lines (RRCL) and primary tumour-cells derived from patients with B-cell lymphomas (N=39). Obatoclax also enhanced the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 52 publications
(67 reference statements)
4
36
0
Order By: Relevance
“…The efficacy of GX15-070 in reducing the ATP production of PHD3-underexpressing cells might however be explained by the fact that GX15-070 treatment downregulates the overall abundance of MCL-1 protein (41). Obviously, we do not want to rule out that GX15-070 affects ATP production in PHD3-underexpressing cells via mechanisms distinct from the effects of mitochondrial MCL-1 (42,43). Taken together, our analyses identified MCL-1 as a novel molecular player, regulating tumor cell metabolism and invasion downstream PHD3.…”
Section: Discussionmentioning
confidence: 94%
“…The efficacy of GX15-070 in reducing the ATP production of PHD3-underexpressing cells might however be explained by the fact that GX15-070 treatment downregulates the overall abundance of MCL-1 protein (41). Obviously, we do not want to rule out that GX15-070 affects ATP production in PHD3-underexpressing cells via mechanisms distinct from the effects of mitochondrial MCL-1 (42,43). Taken together, our analyses identified MCL-1 as a novel molecular player, regulating tumor cell metabolism and invasion downstream PHD3.…”
Section: Discussionmentioning
confidence: 94%
“…21,22 Neoplastic B cells were isolated from pretreatment biopsy tissue obtained from patients with B-cell non-Hodgkin lymphoma or lymphocyte-predominant Hodgkin lymphoma receiving therapy at Roswell Park Cancer Institute (RPCI) as previously described. 23 …”
Section: Cell Lines and Primary Tumor Cellsmentioning
confidence: 99%
“…Notably, it was shown that Bcl-2 antisense enhances the in vitro and in vivo response of EBV-associated lymphoproliferative diseases to the anti-CD 20 antibody rituximab [33], a treatment which is frequently considered in PTLD patients and has been shown to be effective in other B cell malignancies (reviewed by Masood et al [34]). Recent studies on new generation molecules with anti-Bcl-2 reactivity report on their potentiating role of chemotherapeutic activity, as well as on anti-CD 20 antibody, making this easily applicable molecule an ideal predictive marker [35]. …”
Section: Discussionmentioning
confidence: 99%